Rights of future interest as matrimonial property: special reference to earning capacity - Ibrahim, Norliah; Abdul Ghadas, Zuhairah Ariff (International Islamic University Malaysia, 2014)
Traditionally, the claims of matrimonial property are mainly confined to existing and personal property which exist or were acquired during the marriage prior to the divorce, such as buildings, land, vehicles, etc. However, with the changes in the economic sources and social behaviour of the modern society, whereby earnings and proprietary rights are no longer confined to merely property but also include future interest and future earnings such as investments, trust fund and business ventures, it is perceived that the scope of claims on matrimonial property shall also be revolutionised to include claims in future earnings of the divorced parties. This paper discusses the legal principle which the court could apply when it comes to claims on future interest as matrimonial property. The case law analysis is merely confined to the Malaysian precedents and the analogy of human capital earnings is used by the writers to justify the possibility of claims in all types of future earnings as matrimonial property